2011
DOI: 10.1158/0008-5472.can-11-1261
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages Mediate Immunosuppression in the Renal Cancer Microenvironment by Activating the 15-Lipoxygenase-2 Pathway

Abstract: Renal cell carcinoma (RCC), the most common human kidney cancer, is frequently infiltrated with tumorassociated macrophages (TAM) that can promote malignant progression. Here, we show that TAMs isolated from human RCC produce substantial amounts of the proinflammatory chemokine CCL2 and immunosuppressive cytokine IL-10, in addition to enhanced eicosanoid production via an activated 15-lipoxygenase-2 (15-LOX2) pathway. TAMs isolated from RCC tumors had a high 15-LOX2 expression and secreted substantial amounts … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
152
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(157 citation statements)
references
References 42 publications
2
152
0
3
Order By: Relevance
“…Recently, it has been suggested that a local production of IL-10 results in a tumor microenvironment that favors cancer cell survival and metastases (23,27). In RCC, IL-10 and IL-10 receptor expression has been correlated with increased incidence of metastasis (28). Nevertheless, the clinical significance of IL-10 and the mechanism of its induction in cancers remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been suggested that a local production of IL-10 results in a tumor microenvironment that favors cancer cell survival and metastases (23,27). In RCC, IL-10 and IL-10 receptor expression has been correlated with increased incidence of metastasis (28). Nevertheless, the clinical significance of IL-10 and the mechanism of its induction in cancers remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As the regulatory functions of T reg is governed by a pivotal transcription factor, Foxp3 in CD4 + T cells, it is not surprising to find that TAMs promote the expression of Foxp3 via IL-10 and TGF-β signaling [4,64,67,68]. Direct evidence also showed the induction of Foxp3 and CTLA4 expression in CD4 + T cells by TAMs in human renal cell carcinoma in vivo, further emphasizing the critical role of TAMs in cancer-related inflammation, immunosuppression and malignant progression [69].…”
Section: Recruitment Of Other Immunosuppressive Cellsmentioning
confidence: 99%
“…Это объ-ясняется экспрессией мембранной формы M-CSF на поверхности опухолевых клеток [31]. Другое иссле-дование, описывающее популяцию МАО, изолирован-ную из опухолей почки, выделяет экспрессию CD68 и CD163, но не CD206 на поверхности макрофагов [32]. Далее в своем исследовании авторы показали, что МАО, изолированные из опухоли, продуцируют значительное количество CCL-2 -СС-хемокина, ко-торый привлекает новые моноциты в опухоль.…”
unclassified
“…В то же время эти макрофаги продуцируют большое количест-во ИЛ-10. В частности, авторы продемонстрировали, что МАО из более крупных опухолей продуцируют большее количество ИЛ-10 [32]. В своем исследовании I. Daurkin и соавт.…”
unclassified
See 1 more Smart Citation